2022
DOI: 10.1111/epi.17293
|View full text |Cite
|
Sign up to set email alerts
|

Provoked seizures and status epilepticus in a pediatric population with COVID‐19 disease

Abstract: We are reporting 16 pediatric patients (ages 0-18-years-old) who presented to our urban hospital emergency room with seizures and coronavirus disease 2019 (COVID-19) during the surge of the Omicron variant. There was an increased number of pediatric patients with seizures and COVID-19 during this period as compared to prior COVID-19 surges. The 16 patients ranged in age from 3 months to 12 years of age. Five of the 16 patients (31%) had a prior history of epilepsy.Eight patients (50%) presented in status epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 16 publications
(20 reference statements)
1
30
1
Order By: Relevance
“…The complex febrile seizure proportion in the pandemic was also significantly higher than that of the corresponding pre-pandemic period (15.4%, 28/182 patients). This increased ratio is similar to that reported in a recent study, where an increase in complex febrile seizures in pediatric patients (88%, 14/16 patients) during the resurgence of COVID-19 was observed [9]. However, in two other studies, the proportion of complex febrile seizures to total febrile seizures was reported to be approximately 32% and 22%, respectively [2,10].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The complex febrile seizure proportion in the pandemic was also significantly higher than that of the corresponding pre-pandemic period (15.4%, 28/182 patients). This increased ratio is similar to that reported in a recent study, where an increase in complex febrile seizures in pediatric patients (88%, 14/16 patients) during the resurgence of COVID-19 was observed [9]. However, in two other studies, the proportion of complex febrile seizures to total febrile seizures was reported to be approximately 32% and 22%, respectively [2,10].…”
supporting
confidence: 90%
“…proximately 20% to 30% of all febrile seizures are complex [5,6]. Several cases of febrile seizures have been reported in patients with COVID-19, indicating that SARS-CoV-2 can cause febrile seizures [2,[7][8][9][10].…”
mentioning
confidence: 99%
“…According to this study, most patients presented with simple febrile seizures 26 . In contrast, subsequent studies have mentioned cases presenting febrile seizures of atypical ages and severe complex febrile/provoked seizures like our outcomes 27–29 . In addition, patients without a history of epilepsy presented with status epilepticus have been reported due to Omicron subvariant BA.1 infection in Japan 30 .…”
Section: Discussionmentioning
confidence: 67%
“…A study found that convulsions could be a sign of the Omicron variant in children with COVID-19 [83] . Another study on children with COVID-19 found that the Omicron variant is more likely to be associated with neurologic manifestations such as seizures compared with other COVID-19 virus variants [84] . However, there is still a lack of multicenter and forwardlooking research on the neurological complications caused by specific COVID-19 virus variants.…”
Section: Mechanisms Underlying the Neurologic Complications Of Covid-19mentioning
confidence: 99%